Wellbeing and Self-Transformation in Natural Landscapes - Crowther, Rebecca (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores how natural landscapes are linked to positive mental wellbeing. While natural landscapes have long been represented and portrayed as transformative, the link to mental wellbeing is an area that researchers are still aiming to comprehend. Accompanying five groups of people to rural Scotland, the author considers individual, external and group motivations for journeying from urban environments, examining in what ways these excursions are personally and socially transformative. Far more than traversing mere physical boundaries, this book illustrates the new challenges, experiences, territories and cultures provided by these excursions, firmly anchored in the Scottish countryside. In doing so, the author questions the extent to which people's own narratives link to the perception that the outdoors are positively transformative - and what indeed does have the power to influence transformation. Grounded in extensive qualitative research, this contemplative and ethnographic book will be of interest and value to students and scholars of the outdoors and its connection to wellbeing. Rebecca Crowther is a transdisciplinary ethnographic researcher working between, across and beyond disciplines within the arts, humanities and social sciences. Her research interests lie in the phenomenological experience of natural landscapes.